The Relationship Between Implementation of SBAR Communication Techniques and Patient Safety in ICU and ICCU Departments at Kendari General Hospital - Dina Mariana Larira; Ketut Rasmiati; Fitria Indra Kasih (USN Scientific Journal, 2020)
Patient safety is a spirit in hospital services that guarantees the quality of health services. Effective communication is the key for staff to achieve patient safety. One way to achieve effective communication is by using Situation, Background, Assesement, Recommendation (SBAR). This study aims to determine the relationship between the implementation of SBAR communication techniques with patient safety in the ICU and ICCU rooms of the General Regional Hospital in Kendari 2018.This research is a descriptive analytic study with a cross sectional study approach. The population in this study were 33 ICU and ICCU nurses in General Regional Hospital in Kendri 2018. The sample was 33 respondents, the sampling technique was total sampling. The statistical test used was the Fisher Exact Test. The results showed there was a relationship between the implementation of SBAR communication techniques with patient safety in the ICU and ICCU rooms of of the General Regional Hospital in Kendari which was indicated by the value of ρ value 0.001. It is recommended that this study be continued by using more samples and using research methods with the type of case control. Keywords: implementation of communication, SBAR, patient safety